Functional Characterization of Sports Secretaries of Ceará: Socio-demographic and Organizational Analysis of municipal actions aimed at sport and leisure - Basílio Rommel Almeida Fechine; Thaylane Bastos Santos Fechine; Samara Moura Barreto Abreu; Andreyson Calixto Brito; Márcia de Paula Sousa (Revista Intercontinental de Gestão Desportiva, 2021)
This study aimed to characterize the profile of municipal sport secretaries in the State of Ceará, identifying the sociodemographic, organizational and functional situation of these managers. The methodology used had as a guiding parameter a quantitative, descriptive and exploratory analysis, using a specific questionnaire as a data collection instrument, answered by a sample of 17 municipal secretaries of the state of Ceará, cataloged in the period from 2017 to 2019 at random, by search and response, via democratic consent. For the descriptive and statistical interpretation of the variables, Microsoft Office Excel 2020 and SPSS 2020 were used. Among the results found, it was evidenced that the managers of Ceará were mostly male, with an average age between 31 and 40 years old, married, with a college degree/post-graduate course and natives of the municipality, with the development of their work functions carried out in specific sports secretaries. The records signaled the need for the inclusion of women in the field of municipal sports management, via the creation of public policies that encourage the valorization of the female sex. Thus, social projects must be implemented to strengthen the aforementioned public from early childhood, strengthening the triad of dissemination of these values, primarily initiated in the family environment, and secondarily in school and later grounded in the academic field as an inviolable attribute of universal knowledge.